Chromophore Structure in the Photocycle of the Cyanobacterial Phytochrome Cph1 - van Thor, Jasper J. (Biophysical Society, 2006)
The chromophore conformations of the red and far red light induced product states “Pfr” and “Pr” of the N-terminal photoreceptor domain Cph1-N515 from Synechocystis 6803 have been investigated by NMR spectroscopy, using specific (13)C isotope substitutions in the chromophore. (13)C-NMR spectroscopy in the Pfr and Pr states indicated reversible chemical shift differences predominantly of the C(4) carbon in ring A of the phycocyanobilin chromophore, in contrast to differences of C(15) and C(5), which were much less pronounced. Ab initio calculations of the isotropic shielding and optical transition energies identify a region for C(4)-C(5)-C(6)-N(2) dihedral angle changes where deshielding of C(4) is correlated with red-shifted absorption. These could occur during thermal reactions on microsecond and millisecond timescales after excitation of Pr which are associated with red-shifted absorption. A reaction pathway involving a hula-twist at C(5) could satisfy the observed NMR and visible absorption changes. Alternatively, C(15) Z-E photoisomerization, although expected to lead to a small change of the chemical shift of C(15), in addition to changes of the C(4)-C(5)-C(6)-N(2) dihedral angle could be consistent with visible absorption changes and the chemical shift difference at C(4). NMR spectroscopy of a (13)C-labeled chromopeptide provided indication for broadening due to conformational exchange reactions in the intact photoreceptor domain, which is more pronounced for the C- and D-rings of the chromophore. This broadening was also evident in the F2 hydrogen dimension from heteronuclear (1)H-(13)C HSQC spectroscopy, which did not detect resonances for the (13)C(5)-H, (13)C(10)-H, and (13)C(15)-H hydrogen atoms whereas strong signals were detected for the (13)C-labeled chromopeptide. The most pronounced (13)C-chemical shift difference between chromopeptide and intact receptor domain was that of the (13)C(4)-resonance, which could be consistent with an increased conformational energy of the C(4)-C(5)-C(6)-N(2) dihedral angle in the intact protein in the Pr state. Nuclear Overhauser effect spectroscopy experiments of the (13)C-labeled chromopeptide, where chromophore-protein interactions are expected to be reduced, were consistent with a ZZZssa conformation, which has also been found for the biliverdin chromophore in the x-ray structure of a fragment of Deinococcus radiodurans bacteriophytochrome in the Pr form.